Integrating Social Work into Adult Special Care Dentistry - An Interdisciplinary Approach to Care - Michelle Luong; Meagan Smith-Bocanegra; Adam Valdivia; Kelly Vitzthum; Reeva C. Mincer; Michael Lee O'Hara; Eric C. Sung (Taylor & Francis Group, 2023)
ABSTRACTPatients with Special Health Care Needs (SHCN) encounter many barriers in achieving optimal health. This includes primary care, mental health, and oral health. Social workers are adept at addressing these barriers and are trained to provide additional assistance such as emotional counseling, clinical case management, community resource navigation, patient education, and anticipatory guidance. While their assistance is well documented in medical care and hospital settings, collaboration between dentistry and social work is less common. The initiation and integration of a social worker program in dentistry that focused on patients with SHCNs was examined. It was found that social work integration allowed for improved identification of unmet psychosocial needs and decreased barriers to care. As a result, initial appointment attendance rates increased post-integration. Social work in a dental setting has demonstrated the ability to improve bio-psychosocial wellbeing in patients and families, helping address unmet social and psychological needs and reducing barriers to oral health care.